Should Biodiversity be Useful? Scope and Limits of Ecosystem Services as an Argument for Biodiversity Conservation. (April 2015) - Deliège, Glenn; Neuteleers, Stijn
This article examines the argument that biodiversity is crucial for well-functioning ecosystems and that such ecosystems provide important goods and services to our human societies, in short the ecosystem services argument (ESA). While the ESA can be a powerful argument for nature preservation, we argue that its dominant functionalist interpretation is confronted with three sig-nificant problems. First, the ESA seems unable to preserve the nature it claims to preserve. Second, the ESA cannot explain why those caring about nature want to preserve it. Third, the ESA might undermine its own goal because it potentially decreases environmental motivations.